Analisis Sistem Informasi Akuntansi Penggajian Pegawai Untuk Mendukung Pengendalian Intern Pada LARISPA Indonesia - Qorisya Fahzira; Murni Dahlena Nasution (Forum Kerjasama Pendidikan Tinggi, 2022)
Having qualified employees will make a work efficiently. In achieving company goals, it is also influenced by technological developments that are increasing. Creating a payroll system is one of the things that is needed and will be carried out by companies to manage their employees. This study aims to examine the payroll accounting information system of Larispa Indonesia and determine how to implement it. Evaluate its implementation whether it supports internal control. This study uses a qualitative descriptive analysis technique with data collection methods, interviews and documentation. The payroll accounting information system that is implemented at Larispa Indonesia supports all internal controls related to payroll because it has shown its responsibilities. However, there are still dual tasks carried out by the accounting function, namely making employee attendance lists and recording employee salaries but also transferring money to each employee's account. The accounting records at LARISPA Indonesia are not yet effective due to the absence of general journal and ledger records, which only have employee income cards.